Assessment of Borehole Water Quality for Drinking Purposes in Kosa Village - Abhar, Umiyati; Husain , Thamri; Altarans , Indra (PT. Sangadji Media Publishing, 2025)
Access to safe drinking water remains a major challenge in many rural communities, including Kosa Village in Tidore Kepulauan, North Maluku, where borehole wells serve as the primary water source for domestic use. This study aims to assess the physical, chemical, and microbiological quality of borehole water in three hamlets of Kosa Village and to identify the potential factors contributing to water discoloration and odor frequently reported by residents. A descriptive analytical design was employed, and water samples were collected and analyzed at the UPT Puskesmas Soasio Laboratory from March to July 2025, following standardized APHA procedures. The results show that all sampling locations failed to meet national drinking water standards (PERMENKES No. 2/2023) for several physical parameters, including odor, color, turbidity, temperature, and Total Dissolved Solids (TDS). Chemical analysis indicated that residual chlorine levels in Hamlet 1 exceeded permissible limits (0.8 mg/L), while all other chemical and microbiological parameters in Hamlets 2 and 3 remained within the acceptable range. The deterioration in physical quality across all hamlets is likely influenced by geological characteristics, high iron and manganese content, domestic waste infiltration, and inadequate well maintenance. The findings highlight the need for regular monitoring, community-based water treatment strategies, and improved sanitation practices to ensure safe and sustainable access to drinking water in Kosa Village.